DESCRIPTION OF HEMATOCRIT VALUE IN TUBERCULOSIS (TB) PATIENTS RECEIVING ANTI-DRUGS TREATMENT TUBERCULOSIS IN RAYA PUSKESMAS 2019 INTERMEDIATE MATERIALS - Hanindiya, Beta; Feinberg, Bob; Mustaruddin, Mustaruddin; Sanjaya, Muhartri; Samosir, Wilson (Universitas Efarina, 2020)
Tuberculosis is a direct infectious disease caused by the bacterium Microbacterium Tuberculosis. Transmission occurs when a TB patient coughs or sneezes, the germs are spread in the air in the form of sputum droplets (droplet nuclei). The use of OAT in TB patients based on the duration of OAT consumption can cause a decrease in hematocrit values due to side effects of the drug, namely anemia and thrombocytopenia. The method used in this research is descriptive. This study aims to describe the hematocrit value of TB patients receiving OAT treatment at the Raya Pematangsiantar Health Center. The sample of this research is 30 people taken by purposive sampling. The results of the study showed that 24 people (80%) received OAT treatment at the end of the second month, where the examination results showed that 15 people (62.5%) had low hematocrit values, and 9 people (37.5%) were normal. ) shows a low hematocrit value. At the examination of patients receiving treatment at the end of the sixth month, 6 people (20%) showed that the results of the examination with low hematocrit values were 6 people (100%). The low hematocrit value found in TB patients on treatment at the end of the second and sixth months is due to the side effects of the OAT consumed, age, sex and immunity against bacteria that attack blood cells resulting in a decrease in the value of the hematocrit. It can be concluded that of the 30 TB patients who received OAT treatment at the end of the second and sixth months, the number of patients with low hematocrit values was more than those with normal hematocrit values. Therefore it is suggested to the public to be able to follow the treatment procedures that have been recommended especially for TB sufferers.